Effectiveness of Self-differentiation Training Based on Bowen's Approach on Positive Feeling Towards Spouse in Married Women in Isfahan in 2019 - Fariba Saadat mehr; sahar khanjani Veshki (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: As self-differentiation is a process that reflects one's independence in the emotional and rational dimension, in which one learns to make independent decisions and to have a rational love, affection, and intimacy. This research aimed to study the effectiveness of self-differentiation training based on Bowen's approach on positive feelings toward spouse in Married women in Isfahan. Methods: The research method was quasi-experimental with a pretest-posttest design conducted on the control group. The statistical population consisted of counseling applicant women in the city of Isfahan in 2019. Sampling was voluntary. The announcement was installed at counseling centers, and 30 women were randomly placed into control and experiment groups. All participants filled out demographic and Positive Feeling (PFQ) questionnaires. Then, participants of the experiment group were trained in Bowen's self-differentiation in eight sessions. Data analysis was carried out using descriptive (Mean and standard deviation) and inferential statistical methods (analysis of covariance) at the error level of 0.05 and SPSS-24 software. Results: The results indicated that teaching Bowen's self-differentiation significantly affected women's positive feelings towards the spouse (p<0.05), which means that the differentiation training increases the positive feeling towards the spouse. Conclusion: According to the results, teaching Bowen's self-differentiation can increase positive feelings towards spouses in women. Therefore, this technique can be considered a marital problem.